Structure refinement and crystal chemistry of tokkoite and tinaksite from the Murun massif (Russia). (1st April 2017) - Lacalamita, M.; Mesto, E.; Kaneva, E.; Scordari, F.; Pedrazzi, G.; Vladykin, N.; Schingaro, E.
The structures of tokkoite, K2Ca4[Si7O18OH](OH, F) and tinaksite, K2Ca2NaTi[Si7O18OH]O from the Murun massif (Russia) were refined from single-crystal X-ray diffraction data in the triclinic space group P1. Average crystallographic data are a ≈ 10.423, b ≈ 12.477, c ≈ 7.112 Å, α ≈ 89.92°, β ≈ 99.68°, γ ≈ 92.97°, V ≈ 910.5 Å3 for tokkoite; a ≈ 10.373, b ≈ 12.176, c ≈ 7.057 Å, α ≈ 90.82°, β ≈ 99.22°, γ ≈ 92.80°, V ≈ 878.5 Å3 for tinaksite. The substantial similarities between the geometrical parameters of the tokkoite and tinaksite structures led us to conclude that the two minerals are isostructural. However, major differences of tokkoite with respect to tinaksite are larger lattice constants, especially concerning the b parameter, longer distances, especially ; larger values of the M1–M3 and O20–O2 bond lengths, and a stronger distortion of the M1 polyhedron. Mössbauer analysis showed that significant trivalent iron is present, VIFe3+ 40.0(7)% in tokkoite and 12.8(3)% in tinaksite. It is confirmed that 2Ca2+(M1+M2) + (F, OH)–(O20) ↔ Ti4+(M1) + Na+(M2) + O–(O20) is the exchange reaction that describes the relation between tokkoite and tinaksite. In addition, this exchange reaction causes local stress involving mainly the M1 site and its interaction with the M2 and M3 sites.